A new case of white-sutton syndrome associated with celiac disease - Tabaku, Mirela; Tomori, Sonila; Dervishi, Ermira; Rolfs, Arndt; Beetz, Christian; Cullufi, Paskal Cullufi1 (Journal of Biological Studies, 2022)
White-Sutton syndrome (WHSUS) is a neurodevelopmental genetic disorder caused by de novo heterozygous pathogenic variants in the POGZ gene. The phenotypic spectrum of the WHSUS is very broad and mainly includes a wide range of neurocognitive and neurobehavioral symptoms, developmental delays, hypotonia, autism spectrum disorder, typical facial features, and functional and anatomical gastrointestinal anomalies. We describe a new WHSUS patient harboring a novel, heterozygous, de novo, likely pathogenic variant in the POGZ gene highlighting various components of his neurodevelopment, such as the presence of autistic spectrum disorders, speech and mental delays and the association of WHSUS with celiac disease (CD) that has never been described to our best of knowledge. Knowing that gastrointestinal symptoms are one of the most common WHSUS clinical findings, it becomes critical to carefully analyze these symptoms and, in some cases, to start with a CD screening to see whether they are consistent with celiac disease and if CD could be another WHSUS comorbidity, thus broadening the phenotypic spectrum of WHSUS.